Feedback-Based Eco-Design for Integrating the Recency, Frequency, and Monetary Value of Eco-Efficiency into Sustainability Management - Rui Yang Chen (Systems, 2016)
Customer feedback is used to understand customer requirements. Early design phases require the consideration of items including manufacturing, the environment, and sustainability management. Therefore, it is crucial that eco-efficiency is taken into account in the early design phases. Traditionally, eco-efficiency is considered only in terms of eco-design issues, not customer requirements based on business values such as Recency, Frequency, and Monetary (RFM) value. In the meantime, integrating innovation from eco-design is one important aspect. Here, I propose that customer feedback-based eco-efficiency and TRIZ-based innovation can be considered in early eco-design based on the RFM value for sustainability management. The analytic hierarchy process (AHP) and fuzzy-based AHP were integrated to explore the relative weights of RFM variables for business value evaluation. The innovative method of the paper is using a TRIZ contradiction matrix associated with engineering parameters for eco-design. The experimental study has been carried out, and it meets the forecasting business value for green product usage. The business value was used as the decision-making factor in order to evaluate both environmental and marketing performance.